THE EFFECT OF GAME-BASED LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN THE SUBJECT OF SCIENCES IN GRADE IV OF STATE ELEMENTARY SCHOOL 040544 DOLAT RAYAT - Ginting, Milla Aprillianda Br; Ginting, Nurlia; Barus, Julius Boy Nesra Basgimata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning in elementary schools is often teacher-centered, leading students to be less active, quickly bored, and to experience suboptimal learning outcomes. This study aims to determine the effect of the Game-Based Learning model on the learning outcomes of fourth-grade students in Science at SD Negeri 040544 Dolat Rayat. The study used a quantitative, quasi-experimental design with a pretest-posttest control group. The research sample comprised 36 students: 20 in the experimental class and 16 in the control class. The main instrument was a 20-item learning outcome test that had undergone validity and reliability testing, with pretest reliability of 0.721 and posttest reliabilities of 0.681 and 0.723 for standardized items. Data analysis was carried out descriptively and inferentially using the Shapiro-Wilk normality test, the homogeneity test, the paired-samples t-test, and the independent-samples t-test. The results showed that the experimental class's average score increased from 52.75 to 86.05, while the control class's average score increased from 62.19 to 76.94. The hypothesis test shows a significance value of 0.000 and 0.001, as well as the independent-samples t-test post hoc test with a significance value of 0.000, indicating a significant effect of the Game-Based Learning model on students' science learning outcomes.